Sulfur dioxide attenuates LPS-induced acute lung injury via enhancing polymorphonuclear neutrophil apoptosis - Ma Hui-jie; Huang Xin-li; Liu Yan; Fan Ya-min (Acta Pharmacologica Sinica, 2016)
Aim: We speculated that the enhanced apoptosis of polymorphonuclear neutrophil (PMN) might be responsible for the inhibition of PMN infiltration in the lung. This study was designed to investigate the effects of sulfur dioxide (SO2) on PMN apoptosis in vivo and in vitro, which may mediate the protective action of SO2 on pulmonary diseases. Methods: Acute lung injury (ALI) was induced by intratracheally instillation of lipopolysaccharide (LPS, 100 μg/100 g, in 200 μL saline) in adult male SD rats. SO2 solution (25 μmol/kg) was administered intraperitoneally 30 min before LPS treatment. The rats were killed 6 h after LPS treatment. Lung tissues were collected for histopathologic study and SO2 concentration assay. Bronchoalveolar lavage fluid (BALF) was collected for the measurement of PMN apoptosis. For in vitro experiments, rat peripheral blood PMNs were cultured and treated with LPS (30 mg/L) and SO2 (10, 20 and 30 μmol/L) for 6 h, and apoptosis-related protein expression was detected by Western blotting, and apoptosis rate was measured with flow cytometry. Results: LPS treatment significantly reduced the SO2 concentrations in the lung tissue and peripheral blood, as compared with the control group. Pretreatment with SO2 prevented LPS-induced reduction of the SO2 concentration in the lung tissue and peripheral blood. LPS treatment significantly reduced PMN apoptosis both in vivo and in vitro, which could be prevented by the pretreatment with SO2. The protein levels of Caspase-3 and Bax was significantly increased, but Bcl-2 was decreased by the pretreatment with SO2, as compared with LPS administration alone. Conclusion: SO2 plays an important role as the modulator of PMN apoptosis during LPS-induced ALI, which might be one of the mechanisms underlying the protective action of SO2 on pulmonary diseases.